Can Caffeine Be an Effective Ergogenic Aid in Combat Sports? A Comprehensive Review - Marcin Komorowski; Michał Janiszewski; Aleksandra Pelczarska; Rafal Kaczorowski; Tomasz Forenc; Jaromir Hunia; Julia Górny; Jonasz Jurek; Alicja Kapciak (Journal of Education, Health and Sport)
Introduction: Caffeine, a well-known stimulant, is commonly used by athletes to enhance performance across various sports, including combat sports. Its ergogenic properties, such as improved strength, endurance, and cognitive function, have been well documented in the literature. This paper explores the effects of caffeine supplementation on combat sports, specifically in disciplines such as judo, jiu-jitsu, taekwondo, and boxing. The impact of different doses of caffeine on performance in these sports is examined, along with potential risks, limitations, and considerations for its use.